2016
DOI: 10.1038/jp.2016.115
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and bronchopulmonary dysplasia in preterm infants

Abstract: Background Vitamin D deficiency is associated with asthma and reactive airway disease in childhood but its potential contribution to bronchopulmonary dysplasia (BPD) in preterm infants is unknown. Preterm infants have lower levels of 25-hydroxyvitamin D (25[OH]D) at birth and are at risk for nutritional deficiencies after birth. Objective To evaluate the association of 25(OH) D concentrations at birth and at 36 weeks corrected gestational age with BPD in preterm infants born prior to 29 completed weeks of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 38 publications
2
33
2
1
Order By: Relevance
“…Even by removing the effect of intervening factors (gestational age, first minute Apgar score and fifth minute Apgar score), vitamin D deficiency could predict the death of infants, which is consistent with the study by Yang et al (27). In contrast to this, the studies by Joung et al and Onwuneme et al, showed no relationship between the risk of death among succumbed premature infants and the level of vitamin D [(OH)-D] in the umbilical cord (14,28). In these studies, all neonates had normal levels of vitamin D, but in our study, four-fifths of newborns had vitamin D deficiency.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Even by removing the effect of intervening factors (gestational age, first minute Apgar score and fifth minute Apgar score), vitamin D deficiency could predict the death of infants, which is consistent with the study by Yang et al (27). In contrast to this, the studies by Joung et al and Onwuneme et al, showed no relationship between the risk of death among succumbed premature infants and the level of vitamin D [(OH)-D] in the umbilical cord (14,28). In these studies, all neonates had normal levels of vitamin D, but in our study, four-fifths of newborns had vitamin D deficiency.…”
Section: Discussionsupporting
confidence: 87%
“…Vitamin D affects the relationship between endodermal and mesodermal cells that results in alveolar structure and lung maturation. Deficiency of this vitamin, followed by lung non-maturation, may cause the more need for oxygen therapy (14,31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some epidemiological studies have associated neonatal hypovitaminosis D with risk of wheezing, asthma and respiratory tract infections later in infancy [55]. A prospective observational study correlating cord blood and 36-weeks corrected age 25OH-vitD levels in extremely preterm infants with odds of BPD failed to show any association, although most enrolled subjects did not reach vitamin D insufficiency levels (30/33 ng/mL at birth in the BPD and no-BPD groups, respectively) [56]. Interestingly, a similar study conducted in another environment with low/insufficient maternal and neonatal levels yielded opposite results (i.e., a significant correlation between maternal and neonatal levels between BPD/noBPD groups (19/28 and 15/7 ng/mL, respectively) [57]).…”
Section: Micronutrientsmentioning
confidence: 97%